Determinants of the approval of the annual accounts of the municipalities by the Audit Courts: an analysis based on the Human Capital TheoryDeterminantes da aprovação das contas anuais dos municípios pelos Tribunais de Contas: uma análise baseada na Teoria do Capital Humano - Silva, Gabriella Wyara Lopes da; Lima, Victor Godeiro; Matos, Nyalle; Gonçalves, Andrea Oliveira (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2020)
This research seeks to verify if the previous experience and education level of the mayor of a municipality are related to the approval or disapproval of the annual reports judged by the Tribunal de Contas do Rio Grande do Norte (TCE/RN). The personal characteristics of the mayors were collected through the website of the Tribunal Superior Eleitoral (TSE); the results of the judgement of the annual reports on the TCE/RN website; and the previous experience by crossing information from the TSE, TCE/RN and their respective municipalities websites. By comparing the score – calculated through the number of approved reports - which each mayor acquired with their characteristics demonstrated that the TCE/RN has a greater predisposition to approve the accounts of a female candidates with higher level of education, that is young and is associated with a right-wing party.